Point prevalence and sex-specific associated factors of depression in Latvian general population - Vinogradova, Vineta Viktorija; Kivite-Urtane, Anda; Vrublevska, Jelena; Rancans, Elmars (Frontiers in Psychiatry, 2023)
Background: This cross-sectional study aimed to determine the current prevalence of depression, and analyze sex-specific associated socio-demographic and health-related factors for depression in a representative sample of the general adult population of Latvia. Methods: Specially trained professional interviewers conducted computer-assisted face-to-face interviews with a multistage stratified probability sample from the general Latvian adult population (n=2687). A 9-item Patient Health Questionnaire (PHQ) was used for assessment of depression. Respondents were interviewed using the specially developed questionnaire about sociodemographic factors as well as the alcohol use disorder module of the Mini International Neuropsychiatric Interview. Binary logistic regression was used to calculate the odds ratios (OR) for the univariate and multivariate logistic analyses. Results: The point prevalence of depression according to the PHQ-9 was 6.4% (95% CI 5.8-7.6). After adjustment for all independent variables analyzed, being divorced, widowed, or living separately increased the odds of depression [aOR 2.6 (95% CI, 1.2–5.8), p=0.02] in males. For females, unfinished primary education [aOR 5.2 (95% CI 2.0–13.6), p= 0.001] and economically inactive status [aOR 2.0 (95% CI, 1.1–3.6), p=0.03] were strongly associated with depression. Limitations: The cross-sectional design of the study did not allow us to draw conclusions about causality. Patients with bipolar, organic, and symptomatic depression states were not excluded. Conclusions: The prevalence of depression in the general adult population is 6.4%, with the most significant sex-specific factors associated with depression for males - being divorced, widowed, or living separately, and for females it was poor education and economic inactivity.